2017
DOI: 10.4209/aaqr.2016.04.0138
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Endocrine Disruptors and Particulate Matter Emissions from Laser Cutting of Plastic Film in the TFT-LCD Industry

Abstract: In the last five years laser cutting has been identified as one of the solutions for converting and shaping the plastic films used in the Thin Film Transistor Liquid Crystal Display (TFT-LCD) industry due to its positive effects on cost management. However, there has been quite limited information available with regard to the hazards of the air pollutants released during the laser cutting process, and in particular in relation to the real operations that occur in a factory. This is the first study that aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, recent epidemiological studies conducted in a photolithography industry have shown that long-term exposure to ethanol and acetone might result in workers with irregular menstrual cycles and endocrine disruption (Hsieh et al, 2005;Lin et al, 2013a). In a liquid crystal display (LCD) manufacturing factory, longterm exposures to multiple chemicals of low levels might lead to premenopausal female workers with modest changes in their reproductive hormone urinary concentrations (Lin et al, 2013b;Chan et al, 2017). A slightly increase in kidney dysfunction risk was identified for workers in a TFT-LCD industry (simultaneously exposed to IPA, PGMEA, and propylene glycol monomethyl ether (PGME)) with their total exposure levels ≥ 50 ppb for 3-5 years (Chang et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent epidemiological studies conducted in a photolithography industry have shown that long-term exposure to ethanol and acetone might result in workers with irregular menstrual cycles and endocrine disruption (Hsieh et al, 2005;Lin et al, 2013a). In a liquid crystal display (LCD) manufacturing factory, longterm exposures to multiple chemicals of low levels might lead to premenopausal female workers with modest changes in their reproductive hormone urinary concentrations (Lin et al, 2013b;Chan et al, 2017). A slightly increase in kidney dysfunction risk was identified for workers in a TFT-LCD industry (simultaneously exposed to IPA, PGMEA, and propylene glycol monomethyl ether (PGME)) with their total exposure levels ≥ 50 ppb for 3-5 years (Chang et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%